PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) BERBASIS PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS IV SDN 04 NANGA PINOH - Wahyu Septiadi; Clarry Sada; Rosalyna Yoesi Etiovia (JURNAL PENDIDIKAN DASAR, 2016)
Abstract: The objectives of the research are to: 1) to describe the study result of students in learning Indonesian language after applying the cooperative learning model type NHT withscientific-based approach; 2) To describe the study result of students in learning Indonesian after applying the conventional learning model; 3) To observe the differences in Indonesian study result which is applied by using cooperative learning model type NHT withscientific-based approach and  from the application of conventional learning model. The type of this research was Quasy Experimental Design which used The Nonequivalent Control Group Design form. The study used two classes: experimental class and control class. The population in this research were the fourth grade students of Public Elementary School Number 04 Nanga Pinoh. The sample in this research were class IV A and class IV B. The result of research showed that there were differences of study resultprior and following the application of cooperative learning model type Numbered Heads Together (NHT) with scientific-based approach. Prior the application of cooperative learning model type Numbered Heads Together (NHT)  with scientific-based approach, the value obtained t count = 1,240 t table = 2.024. Meanwhile, subsequent to the application of cooperative learning model type Numbered Heads Together (NHT) with scientific-based approach the value obtained t arithmetic = 2.406 t table = 2.024.Keywords: numbered heads together (nht), scientific-based approach,Abstrak: Tujuan penelitian adalah untuk: 1) Mendeskripsikan hasil belajar siswa dalam pembelajaran bahasa Indonesia setelah di terapkan model pembelajaran kooperatif tipe NHT berbasis pendekatan saintifik; 2) Mendeskripsikan hasil belajar siswa dalam pembelajaran bahasa Indonesia setelah di terapkan model pembelajaran konvensional; 3) Mengamati perbedaan hasil belajar bahasa Indonesia yang diterapkan menggunakan model pembelajaran kooperatif tipe NHT berbasis pendekatan saintifik dan penerapan model pembelajaran konvensional. Jenis penelitian ini adalah Quasy Eksperimental Design menggunakan bentuk The Nonequivalent Control Group Design. Penelitian menggunakan dua kelas yaitu kelas eksperimen dan kelas kontrol. Populasi  dalam  penelitian  ini  adalah siswa kelas IV SDN 04 Nanga Pinoh. Sampel dalam penelitian ini yaitu kelas IV A dan kelas IV B. Hasil penelitian menunjukan bahwa terdapat perbedaan hasil belajar sebelum dan sesudah penerapan model pembelajaran kooperatif tipe Numbered Heads Together (NHT) berbasis pendekatan saintifik. Sebelum dilkukannya penerapan model pembelajaran kooperatif tipe Numbered Heads Together (NHT) berbasis pendekatan saintifik di peroleh t hitung = 1,240 t tabel = 2,024. Sedangkan setelah penerapan model pembelajaran kooperatif tipe Numbered Heads Together (NHT) berbasis pendekatan saintifik diperoleh t hitung = 2,406 t tabel = 2,024.Kata kunci: number heads together (nht), pendekatan saintifik dan hasil belajar bahasa indonesia siswa.